Formação da Nova Geopolítica das Mudanças Climáticas - Moreira, Helena Margarido (Sustainability in Debate, 2013)
This paper presents the evolution on climate change negotiations towards a more inclusive and efficient global agreement, and how the main countries position and group themselves, to show that the geopolitical configuration of climate change has been changed. North-South divergence, settled in terms of development, shaped for a long time the course of negotiations, including the basis for the structure of the international environmental order of climate change through the “common but differentiated responsibilities” principle. However, the present state of climate negotiations shows that such North-South division gave place to an assembly of countries defined in terms of spatialization of greenhouse gases emissions. A greater scientific knowledge on the causes and consequences of climate change, raised by the research and reports published by IPCC, and a shift on the world scenery defined by the power games between great powers are elements that help us to investigate a shift on climate change geopolitics. The geopolitics we observe nowadays opposes the great GHG emitters to countries with expressive and growing emissions, but that are not able, separately or in small groups, of exerting power enough, at a global level, to alter international outcomes.